Seams of Empire : Race and Radicalism in Puerto Rico and the United States - Alamo-Pastrana, Carlos (Book collections on Project MUSE., 2016)
Using his ideas of racial imbrication (an approach that discerns overlapping layers of racism, colonialism, and exploitation), Alamo highlights the reasons and ways that many Puerto Ricans were marginalized in what has generally been perceived as a progressive space, and he looks at how the island gave American blacks and progressive whites a less restrictive place to generate interest in black radicalism.